Seamounts, canyons and slope: The preference of a new stilipedid amphipod (Crustacea: Amphipoda) for the Bay of Biscay. (30th September 2022) - Frutos, Inmaculada; Sorbe, Jean Claude
Abstract: North Atlantic specimens attributed to the genus Stilipes were first reported by Lagardère in 1977, and subsequently sampled during different research programmes on suprabenthic communities from the southern Bay of Biscay and the Galicia Bank. Their morphological study showed that they belong to a new species to science, discriminated from the four known species S. distinctus Holmes1908; S. lacteus (K.H. Barnard, 1931); S. sanguineus (Hurley, 1954) and S. macquarensis Berge 2003. The new species was sampled in the near-bottom water layer with several multinet suprabenthic sledges. Within its known distributional area, Stilipes lagarderei sp. nov. is living between 462 and 1060 m depth on muddy bottoms in the canyons and on fine and medium sands on the seamounts. This upper bathyal species is very rare with a maximum abundance registered on the Galicia Bank (12.9 ind./100 m 2 ). Considered to be a mesopelagic species, as for its congeners, the data herein presented demonstrate that Stilipes lagarderei sp. nov., colonizes the near-bottom environment, thus exhibiting a suprabenthic behavior. An identification key to the known Stilipes species is provided. Ecological notes and biological comments of the new species are also presented. Highlights: A new deep-sea amphipod species in the Bay of Biscay and Galicia Bank. First record of the genus Stilipes in the North Atlantic Ocean. Bathyal species restricted to medium latitudes in the NE Atlantic Ocean. Suprabenthic behavior in a suspected mesopelagic species.